Razor's edge - Wells, Martha (Star wars, empire and rebellion, 2013)
Princess Leia Organa and Han Solo lead an Alliance delegation to negotiate a deal for much-needed materials for the Rebel Alliance when they fall into the hands of fierce marauders from Leia's homeworld of Alderaan, recently destroyed by the Death Star. Struggling with intense feelings of guilt, loyalty, and betrayal, Leia is determined to help her wayward kinspeople, even as Imperial forces are closing in on her own crippled ship.